Creating a microclimatic thermal mode by the multilevel system for heating industrial structures - Romanchenko, Nikolai; Romanchenko, Vladimir; Kundenko, Nikolai; Sanin, Yuri (Eastern-European Journal of Enterprise Technologies, 2020)
A heating system for predicting the thermal state, to control and regulate the heating of technologically active zones of production facilities has been proposed. This makes it possible to ensure a high-quality level of compliance with the standards of the thermal mode at production facilities through the use of energy-saving multifunctional systems of a multi-level heating system. At the same time, the heating devices of the resistor type are located below the floor level and their heaters are powered by traditional and non-traditional renewable energy sources. Modeling of thermal processes in the heating system, which was reduced to solving the problem of heat conductivity in the flat layer system, was carried out. A constituent part of this solution is to determine the floor surface temperature as a functional series, which establishes a relationship between the standards of floor surface heating and the power of energy flows in a multilevel heating system. This approach makes it possible to ensure the structural and functional control of energy flows and at the same time ensure the responsiveness and accuracy of compliance with the set standards of the thermal parameters of the microclimate of the technologically active area of industrial facilities for various functional purposes